Control biologico del gusano cachon (Erinnyis ello) - Bellotti, Anthony C. (International Center for Tropical Agriculture, 1978)
A program of biological control of the cassava hornworm appears feasible. The following biological control agents have been found to reduce hornworm populations effectively: Trichogramma spp. (egg parasites), Apanteles spp. (larval parasites), Polistes spp. (larval predators) and Bacillus thuringiensis (pathogenic to larvae). Further studies are required to develop the program better and test it at a commercial level. (AS-CIAT)